2003
DOI: 10.1080/03055690303275
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Confidence in Lifelong Learning

Abstract: Bolton BL2 1JW (mn2@bolton.ac.uk/ th3@bolton.ac.uk) 2 AbstractThe key objectives and targets of the Learning and Skills Council's (LSC,2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 18 publications
3
60
0
6
Order By: Relevance
“…Moreover, the trainees' confidence grew as they gained credibility in the role of teacher and this growing sense of confidence is closely connected to the trainees' evolving self-identification as a teacher. Confidence, in this understanding, is subjective and dependent on situation and providing the opportunity for the trainees to enhance their confidence by learning to be confident may be one of the most useful functions of teacher training (Norman and Hyland 2003). Yet, confidence can be considered as primarily about perception of self, not necessarily about enhancing the quality or range of professional practice.…”
Section: Confidencementioning
confidence: 99%
“…Moreover, the trainees' confidence grew as they gained credibility in the role of teacher and this growing sense of confidence is closely connected to the trainees' evolving self-identification as a teacher. Confidence, in this understanding, is subjective and dependent on situation and providing the opportunity for the trainees to enhance their confidence by learning to be confident may be one of the most useful functions of teacher training (Norman and Hyland 2003). Yet, confidence can be considered as primarily about perception of self, not necessarily about enhancing the quality or range of professional practice.…”
Section: Confidencementioning
confidence: 99%
“…Such a negative perception of learning reduces individuals' expectations, motivation and confidence, which McGivney (1993) calls 'a dispositional barrier'. Research has shown that a lack of confidence is very likely to make learners self-critical, doubtful of their abilities, nervous and insecure, reducing their ability to communicate and interact with others (Norman & Hyland, 2003). Such negative feelings prevent them from engaging in lifelong learning activities.…”
Section: Selfmentioning
confidence: 99%
“…It has been suggested that self-confidence can be either a trait or something that is specific to certain situations. Norman & Hyland (2003) point out that if self-confidence is seen as a trait, which personality theorists suggest are relatively stable over time, then those who lack self-confidence would be unlikely to develop it through educational activity. If, however, it is viewed as a situationally specific concept, as is assumed by this new model, then it is possible for students to increase their levels of selfconfidence for any given situation.…”
Section: Reflection and Evaluationmentioning
confidence: 99%